2007
DOI: 10.1186/1471-2474-8-78
|View full text |Cite
|
Sign up to set email alerts
|

Indications for free vascularized fibular grafting for the treatment of osteonecrosis of the femoral head

Abstract: Background: The present study aimed to determine the indications for free vascularized fibular grafting for the treatment of osteonecrosis of the femoral head.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 36 publications
0
59
0
Order By: Relevance
“…It has been proved that most hip-preserving surgery can achieve good outcomes only when the necrotic areas are limited to small parts of the femoral head [29]. Current available treatments focusing on reconstruction of the blood supply of femoral head can frequently largely improve the curative effect [30][31][32][33][34]. So does vascularized greater trochanter flap grafting.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that most hip-preserving surgery can achieve good outcomes only when the necrotic areas are limited to small parts of the femoral head [29]. Current available treatments focusing on reconstruction of the blood supply of femoral head can frequently largely improve the curative effect [30][31][32][33][34]. So does vascularized greater trochanter flap grafting.…”
Section: Discussionmentioning
confidence: 99%
“…Their clinical success rate, reported for 188 cases (224 hips) with an average follow-up of 4.3 years, was 67.4% after 2 years, 64.5% after 5 years, and 63%, overall. Kawate et al, (2007) reported a 7-year success rate of 67%, and indicated that the success rate in patients with preoperative, pre-collapsed ONFH was significantly higher than that in patients with preoperative, collapsed ONFH. However, vascularized bone graft surgery is a long, complex surgery that is more traumatic and subject to significant complications, such as peroneal nerve palsy, post-transplantation subtrochanteric fracture, and ankle pain.…”
Section: Discussionmentioning
confidence: 99%
“…The safety of the procedure was determined by the incidence of postoperative major and minor complications [4,14].…”
Section: Resultsmentioning
confidence: 99%
“…FVFG is an attractive alternative to all the aforementioned options, especially for younger patients without severe osteoarthritis of hip joint [14]. The advantage of FVFG lies in the combination of femoral head decompression, removal of necrotic lesion, introduction of osteoinductive cancellous bone, and vascularised cortical bone support of the subchondral surface [24].…”
Section: Discussionmentioning
confidence: 99%